Is There a Long-Term Link Between Digital Media Use and Adolescent Headaches? A Longitudinal School-Based Study - Clarissa Humberg; Verena Neß; Lisa-Marie Rau; Julia Wager (Children)
Background/Objectives: The use of digital media, and especially social media, has been increasing over recent years. Previous research has reported a negative impact of media use on headaches; however, most of these studies are cross-sectional. Therefore, we conducted a longitudinal study to explore the relationship between different types of media usage (watching videos, gaming, and social media) and headache frequency and headache intensity over time. Methods: School-aged children from five German schools completed five assessments between 2017 and 2018. In total, N = 575 (72.9% female; Mage = 13.3, SDage = 1.86) children and adolescents reporting consistent headaches across all assessments were analyzed. Multilevel linear modeling was used to assess the relationships between media use and headache frequency and intensity over time. Results: There were only minor associations between media use and headache intensity or frequency. Notably, only high social media usage was linked with worse headache intensity (t(1989) = 4.109, p < 0.001). Conclusions: The impact of media use on headaches seems to be less harmful than previous research might suggest. We believe that increased time spent consuming media should not be considered a risk factor for pain conditions but rather a helpful resource for pain management.